The Useful art of the social-economic Rankings - Tomasz Kuszewski; Agata Sielska (Contemporary Economics)
The purpose of the paper is to identify advantages and disadvantages of various methods of constructing rankings. The subject of our study is important due to the international debate on development and welfare measurement methods and ways of comparing results obtained for different countries. Because GDP per capita does not allow sufficient assessment, countries are compared on the basis of many criteria and results are usually presented in form of rankings. We discuss different outranking methods originating from multidimensional statistical analysis and multicriteria optimization and compare them taking into consideration the effect of each method and each set of criteria on the final result. Our remarks are illustrated by rankings of development and economic performance built for European Union countries. Our observations and results can be regarded also as an opinion in the discussion on the report of the International Commission onMeasurement of Economic Performance and Social Progress chaired by J.E. Stiglitz and A. Sen.